Sex‐Specific Associations of Vascular Risk Factors With Abdominal Aortic Aneurysm: Findings From 1.5 Million Women and 0.8 Million Men in the United States and United Kingdom. Issue 4 (18th February 2020) - Carter, Jennifer L.; Morris, Dylan R.; Sherliker, Paul; Clack, Rachel; Lam, Kin Bong Hubert; Halliday, Alison; Clarke, Robert; Lewington, Sarah; Bulbulia, Richard
Abstract : Background: Large studies are required for reliable estimates of important risk factors for abdominal aortic aneurysm (AAA). This could guide targeted AAA screening programs, particularly in subgroups like women who are currently excluded from such programs. Method and Results: In a cross‐sectional study, 1.5 million women and 0.8 million men without known vascular disease attended commercial screening clinics in the United Kingdom or United States from 2008 to 2013. Measurements of vascular risk factors were related to AAA using logistic regression with correction for regression dilution bias. Screening detected 12 729 new AAA cases (0.6%). Compared with never smoking, current smoking was associated with 15 times the risk of AAA among women (risk ratio 15.0, 95% CI 13.2–17.0) and 7 times among men (7.3, 6.4–8.2). In women aged <75 years, the risk of AAA was nearly 30 times greater in current smokers (26.4, 20.3–34.2). In every age group, the prevalence of AAA in female smokers was greater than in male never‐smokers. Positive log‐linear associations with AAA for women and men were also observed for usual body mass index, usual systolic blood pressure, height, usual low‐density lipoprotein cholesterol, and usual triglycerides. Conclusions: Log‐linear increases in the risks of AAA with traditional vascular risk factors should be considered when evaluating populations that may be at‐risk for the development of AAA, and when considering potential treatments. However, at any given age, female smokers are at higher risk of AAA than male never‐smokers, and a policy of screening male never‐smokers but not higher‐risk female smokers is questionable.